Post-Flood Profile of Leptospirosis Cases at Teaching Hospital of Municipal Medical College in Surat City - Rachna Prasad; Vipul Srivastava; RK Bansal; AB Pawar; Vandana Desai; Kalpana Desai; Mannu Jain (Medsci Publications, 2010)
This study reports the clinical profile, pattern of organ involvement and the case fatality of 112 cases of Leptospirosis admitted during an outbreak in the post flood period from August to September 2006 in Surat city. The study reveals the necessity for early detection of cases in an epidemic situation, chemoprophylaxis of those exposed and prompt referral and management with excellent ICU support for decreasing the mortality associated with the disease.